Materials science and processing, environmental engineering and information technologies : selected, peer reviewed papers from the 2014 International Conference on Application of Materials Science and Environmental Materials (AMSEM 2014), July 4-6, 2014, Yichang, Hubei, China - Hegde, Gurumurthy (Applied mechanics and materials, 2014)
Collection of selected, peer reviewed papers from the 2014 International Conference on Application of Materials Science and Environmental Materials (AMSEM 2014), July 4-6, 2014, Yichang, Hubei, China. The 156 papers are grouped as follows: Chapter 1: Materials for Mechanical Engineering and Technologies of Materials Processing, Chapter 2: Building Materials and Construction Technologies, Chapter 3: Chemical Materials and Chemical Engineering, Chapter 4: Environmental Friendly Materials, Chapter 5: Prevention of Pollution the Water Environment and Processing of Wastewater, Chapter 6: Solutions in Environmental Engineering, Chapter 7: Engineering Solutions in Mechanical Engineering, Chapter 8: Applied Information Technologies, Communication and Data Processing Keyword: Material Science, Environmental Material, Water Pollution, Information Technology, Intelligent System Some 160 papers cover materials for mechanical engineering and technologies of material processing; building materials and construction technologies; chemical materials and chemical engineering; environmentally friendly materials; preventing environmental water pollution and processing wastewater; solutions in environmental engineering; engineering solutions in mechanical engineering; and applied information technologies, communication, and data processing. Among specific topics are high-temperature oxidation studies of an aluminum coating deposited by magnetron sputtering, the finite element analysis of a lightweight energy-saving composite floor, the synthesis and characterization of a manganese phosphate alumino-silicate molecular sieve, calculating carbon dioxide emission in Nanjing City and its influencing factors, and the design and drop test of an aircraft landing gear's shock absorber based on a magneto-rheological damper. -- Environmental engineering-- Environmental science-- Materials science.